Stable expression of nucleocapsid proteins of Puumala and Hantaan virus in mammalian cells - Welzel, Tania Mara; Kehm, Roland; Tidona, Christian; Muranyi, Walter; Darai, Gholamreza (Virus genes, 1998)
The development of an in vitro-system for the stable expression and the analysis of native hantavirus proteins using hantaviral cDNA is of particular interest. As a first step the expression of the hantavirus nucleocapsid (N) proteins in mammalian cells was studied in more detail. The cDNA of the S-RNA segment of Puumala virus strain CG-1820 and Hantaan virus strain 76-118 was used for the construction of eucaryotic expression vectors that allow the generation and selection of mammalian cells harboring and expressing the N protein genes of hantaviruses. A variety of conventional and novel expression vectors as well as different mammalian cell lines were screened. The expression of the N protein of Puumala virus using the pGRE5-1 vector in which the transcription is under control of inducible glucocorticoid responsive elements (GRE) revealed that the Puumala virus N protein can be expressed in Vero E6 cells efficiently without any detectable cell toxicity. From the variety of expression vectors tested, it was found that pCR3.1 is the vector of choice for stable expression of hantavirus N proteins. The successful establishment of different mammalian cell lines expressing considerable amounts of Puumala and Hantaan virus N protein indicates that the stable and efficient expression of this particular viral protein in the cell lines of three evolutionary distinct species (human, monkey, and mouse) is possible. The system described here represents the experimental basis for further studies of hantavirus infection, replication, and pathogenesis using a reverse genetics approach.
Gesehen am 29.08.2024